2011
DOI: 10.1136/bmjqs.2010.046532
|View full text |Cite
|
Sign up to set email alerts
|

Clarity and strength of implications for practice in medical journal articles: an exploratory analysis

Abstract: ObjectiveTo examine how leading clinical journals report research findings, aiming to assess how they frame their implications for medical practice and to compare that literature's patterns with those of the management literature.Data SourceClinically relevant research articles from three leading clinical journals (N Engl J Med, JAMA, and Ann Intern Med).MethodsReview of wording of a sequential sample from 2010, with categorisation, comparison among journals, and comparison with management literature.ResultsCl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 61 publications
0
12
0
Order By: Relevance
“…37 If the Discussion were demonstrably reproducible with this parallel approach, the credibility of the implications for medical practice would be enhanced, and suggestions regarding whether or not the findings of a study warranted a change in clinical care. 38 Conversely, a divergent second Discussion would represent a challenge to inferential reproducibility that might prompt a cautious re-evaluation of the original interpretation. Table 2 Continued with a low severity of illness score also demonstrated no beneficial effects.…”
Section: Limitationsmentioning
confidence: 99%
“…37 If the Discussion were demonstrably reproducible with this parallel approach, the credibility of the implications for medical practice would be enhanced, and suggestions regarding whether or not the findings of a study warranted a change in clinical care. 38 Conversely, a divergent second Discussion would represent a challenge to inferential reproducibility that might prompt a cautious re-evaluation of the original interpretation. Table 2 Continued with a low severity of illness score also demonstrated no beneficial effects.…”
Section: Limitationsmentioning
confidence: 99%
“…Joanne Lynn and colleagues, in Clarity and strength of implications for practice in medical journal articles: an exploratory analysis , empirically examined two literatures for practitioners—clinical and management—and found two different norms for recommending action. 13 The majority of original articles from three leading healthcare clinical journals (68.6%) simply stated that one intervention was (or was not) different from another in its effects. Reports in these journals directed a particular action (‘therefore, x should be done’) only 25.5% of the time.…”
Section: Collective Wisdom That Emerged In the Course Of The Meetingmentioning
confidence: 99%
“…Anne Lynn, Allessia Owens and Jean Bartunek have recently explored how three journals ( New England Journal of Medicine, JAMA, and Annals of Internal Medicine ) frame their implications for medical practice 2 . They found that just 25% of the articles they reviewed recommended a specific course of action.…”
mentioning
confidence: 99%
“…The issues raised by Lynn et al. 2 and Fleischacker et al. 3 were echoed in feedback received with HILJ when it canvassed its editorial advisory board and members of the HLG committee and discussion list.…”
mentioning
confidence: 99%
See 1 more Smart Citation